A Concepção de Professores e de Educação no Plano Nacional de Educação: Contribuições a partir da Pedagogia Histórico-Crítica - Martins, Naiady dos Santos (2021)
Education, linked to the other categories which structure the whole social complex that we know, at the same time it possesses relative autonomy, considering that it fulfills a specific role in society, it also suffers the influence of the social whole, from which it cannot be detached. Studying education is, before anything, to understand the humanizing process built by the human gender, requiring an ontological based study, without it the research becomes merely superficial. For this reason, this study searched for, among bibliographical reviews and documentary analysis, studying the concept of education and professors in the National Plan of Education. In chapter 1 it peered at the ontological understanding of education, comprehending that work is the funding category of the social being, from which human beings started having conditions to progress and develop language, advancing through time until feeling the historical need to create educational processes. In chapter 2 we saw that different social institutions throughout the centuries treated education in different ways, observing social influence on education, almost always treated as an exclusive item of the rich. We passed through egypt, greek and roman civilizations until the capitalist rising would have the interest in turning formal education the main form of instructing the work mass, by the own intellectual demands of that society. In chapter 3 we specifically treated of the National Plan of Education, studying it also from an ontological view, first we made a retrospect of the country’s history focusing on the creation of the education plans so it would make it possible to understand how we got to the current National Plan of Education; next, we related some of its goals to the historical, political and social context experienced today, finally pointing out some progress that was achieved especially regarding the fulfilment of its goals and the lack of a theoretical concept, that we consider a lost opportunity on the construction of solid basis to guide the educational politics of the country. Key-words: National Plan of Education; Education; Professors; Historical-Critical Pedagogy.